Transnationalization, the Global Crisis and Foreign Debt: The Philippine Experience - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
This paper attempts to examine some of the crucial aspects, from the perspective of the Philippine experience, the current dilemmas brought about by international economic relations. The impacts of the existence of the OPEC; and the transnationalization of the Philippine economy under the Marcos regime, provide the backdrop for the availability of large amounts of foreign exchange within the country. Simultaneously, Filipinos were opened to an influx of imported consumer goods. As a result, money easily flowed out of the country as quickly as it came in. This problem is further aggravated by the rise in interest rates in the international financial markets. The Marcos government’s borrowing of more loans to cover deficits, lead to the mounting indebtedness of our country. In addition, First World countries have instituted protectionist measures, which have affected Third World exports. The global economic crisis of the 1980’s facilitated for the rise of the IMF and the World Bank. These institutions supervise the adjustment of heavily indebted countries by means of “rescue packages” in the form of conditionalities. The foreign debt of our country by now has amounted to a huge sum that it is impossible to service it completely without having to borrow new money. Furthermore, this economic crisis, an aspect the Philippines shares with other indebted Third World countries, is coupled with an ensuing political crisis. The problem of whether or not democracy can last without concrete changes in the world economic order must be seriously addressed. It is also doubtless if economies of the South will be able to end balance of payments problems unless radical restructuring of international economic relations be made. In conclusion, the paper argues that developing nations, particularly the Philippines, can only meaningfully participate in the world economic system when they have attained a degree of economic autonomy.
Keywords: terms of trade, transnationalization, IMF, Conditionality, foreign debt, autonomy